Genome editing approaches with CRISPR/Cas9: the association of NOX4 expression in breast cancer patients and effectiveness evaluation of different strategies of CRISPR/Cas9 to knockout Nox4 in cancer cells - Marzieh Javadi; Hossein Sazegar; Abbas Doosti (BMC Cancer, 2023)
Abstract Background The increasing prevalence of cancer detection necessitated practical strategies to deliver highly accurate, beneficial, and dependable processed information together with experimental results. We deleted the cancer biomarker NOX4 using three novel genetic knockout (KO) methods. Homology-directed repair (HDR), Dual allele HITI (Du-HITI) and CRISPR-excision were utilized in this study. Methods The predictive value of the NOX4 expression profile was assessed using a combined hazard ratio (HR) with a 95% confidence interval (CI). With a 95% confidence interval, a pooled odd ratio (OR) was used to calculate the relationship between NOX4 expression patterns and cancer metastasis. There were 1060 tumor patients in all sixteen research that made up this meta-analysis. To stop the NOX4 from being transcribed, we employed three different CRISPR/Cas9-mediated knockdown methods. The expression of RNA was assessed using RT-PCR. We employed the CCK-8 assay, colony formation assays, and the invasion transwell test for our experiments measuring cell proliferation and invasion. Using a sphere-formation test, the stemness was determined. Luciferase reporter tests were carried out to verify molecular adhesion. Utilizing RT-qPCR, MTT, and a colony formation assay, the functional effects of NOX4 genetic mutation in CRISPR-excision, CRISPR-HDR, and CRISPR du-HITI knockdown cell lines of breast cancer were verified. Results There were 1060 malignant tumors in the 16 studies that made up this meta-analysis. In the meta-analysis, higher NOX4 expression was linked to both a shorter overall survival rate (HR = 1.93, 95% CI 1.49–2.49, P < 0.001) and a higher percentage of lymph node metastases (OR = 3.22, 95% CI 2.18–4.29, P < 0.001). In breast carcinoma cells, it was discovered that NOX4 was overexpressed, and this increase was linked to a poor prognosis. The gain and loss-of-function assays showed enhanced NOX4 breast carcinoma cell proliferation, sphere-forming capacity, and tumor development. To activate transcription, the transcriptional factor E2F1 also attaches to the promoter region of the Nanog gene. The treatment group (NOX4 ablation) had substantially more significant levels of proapoptotic gene expression than the control group (P < 0.01). Additionally, compared to control cells, mutant cells expressed fewer antiapoptotic genes (P < 0.001). The du-HITI technique incorporated a reporter and a transcription termination marker into the two target alleles. Both donor vector preparation and cell selection were substantially simpler using this approach than with “CRISPR HDR” or “CRISPR excision.“ Furthermore, single-cell knockouts for both genotypes were created when this method was applied in the initial transfection experiment. Conclusions The NOX4 Knockout cell lines generated in this research may be used for additional analytical studies to reveal the entire spectrum of NOX4 activities. The du-HITI method described in this study was easy to employ and could produce homozygous individuals who were knockout for a specific protein of interest.